Dataset for the reporting of carcinoma of the exocrine pancreas: recommendations from the International Collaboration on Cancer Reporting (ICCR). Issue 6 (22nd September 2021) - Verbeke, Caroline; Webster, Fleur; Brosens, Lodewijk; Campbell, Fiona; Del Chiaro, Marco; Esposito, Irene; Feakins, Roger M; Fukushima, Noriyoshi; Gill, Anthony J; Kakar, Sanjay; Kench, James G; Krasinskas, Alyssa M; et al.
Abstract : Aims: Current guidelines for pathology reporting on pancreatic cancer differ in certain aspects, resulting in divergent reporting practices and a lack of comparability of data. Here, we report on a new international dataset for pathology reporting on resection specimens with cancer of the exocrine pancreas (ductal adenocarcinoma and acinar cell carcinoma). The dataset was produced under the auspices of the International Collaboration on Cancer Reporting (ICCR), which is a global alliance of major (inter)national pathology and cancer organisations. Methods and results: According to the ICCR's rigorous process for dataset development, an international expert panel consisting of pancreatic pathologists, a pancreatic surgeon and an oncologist produced a set of core and non‐core data items based on a critical review and discussion of current evidence. Commentary was provided for each data item to explain the rationale for selecting it as a core or non‐core element and its clinical relevance, and to highlight potential areas of disagreement or lack of evidence, in which case a consensus position was formulated. Following international public consultation, the document was finalised and ratified, and the dataset, which includes a synoptic reporting guide, was published on the ICCR website. Conclusions: This first international dataset for cancer of the exocrine pancreas is intended to promote high‐quality, standardised pathology reporting. Its widespread adoption will improve the consistency of reporting, facilitate multidisciplinary communication, and enhance the comparability of data, all of which will help to improve the management of pancreatic cancer patients. Abstract :